POLITIK HUKUM PEMBENTUKAN UNDANG-UNDANG NOMOR 1 TAHUN 2022 TENTANG HUBUNGAN KEUANGAN ANTARA PEMERINTAH PUSAT DAN PEMERINTAHAN DAERAH DALAM PERSPEKTIF OTONOMI DAERAH - Ilham Dwi Mirza; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The establishment of Law Number 1 of 2022 concerning Financial RelationsBetween the Central Government and Regional Governments as a result of the Law hasnot been able to provide a significant leap in improvement to the equitable distributionof public services and public welfare, and has not been optimally aligned andsynergistic in the APBD and APBN, so that national fiscal policy has not workedsignificantly in realizing state goals. The purpose of this study is to explain the legalpolitics of the establishment of Law Number 1 of 2022 concerning Financial RelationsBetween the Central Government and Regional Government in the Perspective ofRegional Autonomy.This research is a normative legal research with a focus on legal principles. Toanswer this research, the author uses qualitative analysis with literature study techniqueson primary legal materials in the form of laws and regulations, secondary legal materialsin the form of legal scientific research results, legal science books, and academicmanuscripts of Law Number 1 of 2022, as well as tertiary legal materials in the form oflarge online Indonesian dictionaries.This study examines and analyzes the urgency in the formation of Law Number1 of 2022 which repeals Law Number 33 of 2004 and Law Number 28 of 2009. Therepeal of the two laws resulted from the need to improve the implementation offinancial relations between the central government and local governments. It isrecommended that the President and the House of Representatives are expected toimmediately ratify and promulgate laws and regulations related to the generalprovisions of the HKPD Law, procedures for collecting taxes and regional levies,procedures for collecting Opsen, tax revenues directed at their use, types of additionalregional levies, and procedures for determining tax rates and levies so that the HKPDLaw can be fully implemented.Keywords: Legal Politics, Fiscal Decentralization, Regional Autonomy